Implementasi Prinsip-Prinsip Syari’ah pada Lembaga Keuangan Syari’ah - Rukaini Rukaini; Juliana Putri (Asosiasi Riset Ekonomi dan Akuntansi Indonesia, 2025)
This study aims to discuss the sharia principles applied in Islamic financial institutions, especially in Islamic banking, which focuses on evaluating the extent to which Islamic principles are implemented. This research method uses library research which involves collecting journal articles that are in accordance with the research topic using descriptive analysis. The data analysis used is inductive analysis. The results of the study indicate that the implementation of sharia principles in Islamic financial institutions is an effort to realize a fairer, more transparent, and sustainable financial system. Although there are several challenges, with a strong commitment from all parties, Islamic banking has great potential to develop and make a positive contribution to society. So that with the implementation of sharia principles in Islamic financial institutions, transactions that are contrary to Islamic teachings can be avoided: such as usury, maisir (gambling), gharar (obscurity), and other prohibited things.